2015
DOI: 10.4062/biomolther.2014.127
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of 3-(4-Hydroxyphenyl)-1-(thiophen-2-yl) prop-2-en-1-one, a Chalcone Derivative on MCP-1 Expression in Macrophages via Inhibition of ROS and Akt Signaling

Abstract: Chalcones (1,3-diaryl-2-propen-1-ones), a subfamily of flavonoid, are widely known to possess potent anti-inflammatory and anti-oxidant properties. In this study, we investigated the effect of 3-(4-Hydroxyphenyl)-1-(thio3-(4-Hydroxyphenyl phen-2-yl)prop-2-en-1-one (TI-I-175), a synthetic chalcone derivative, on endotoxin-induced expression of monocyte chemoattractant protein-1 (MCP-1), one of the key chemokines that regulates migration and infiltration of immune cells, and its potential mechanisms. TII-175 pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Since the initial observations of anti-inflammatory and anti-oxidant activity of chalcones, synthetic modifications of chalcones have been extensively studied in the attempts to develop promising therapeutic agents with enhanced biological activity and less profound side effects. We have previously shown that the synthetic chalcone derivative 3-(4-Hydroxyphenyl)-1-(thiophen-2-yl)prop-2-en-1-one inhibits ROS production and Akt signaling ( Kim et al ., 2015 ) and phenyl/hydroxyphenyl-3-thienylpropenones prevents nitric oxide production through HO-1 induction in macrophages ( Kim et al ., 2014 ). In this study, as part of our ongoing efforts to develop optimal anti-oxidant and anti-inflammatory agents, we prepared a series of chalcone derivatives incorporating hydroxyl and trifluormethyl groups in phenyl-3-thienylpropenones at different positions and evaluated their anti-oxidative properties.…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial observations of anti-inflammatory and anti-oxidant activity of chalcones, synthetic modifications of chalcones have been extensively studied in the attempts to develop promising therapeutic agents with enhanced biological activity and less profound side effects. We have previously shown that the synthetic chalcone derivative 3-(4-Hydroxyphenyl)-1-(thiophen-2-yl)prop-2-en-1-one inhibits ROS production and Akt signaling ( Kim et al ., 2015 ) and phenyl/hydroxyphenyl-3-thienylpropenones prevents nitric oxide production through HO-1 induction in macrophages ( Kim et al ., 2014 ). In this study, as part of our ongoing efforts to develop optimal anti-oxidant and anti-inflammatory agents, we prepared a series of chalcone derivatives incorporating hydroxyl and trifluormethyl groups in phenyl-3-thienylpropenones at different positions and evaluated their anti-oxidative properties.…”
Section: Discussionmentioning
confidence: 99%
“…HEK293 cells transfected with β-galactosidase constructs (0.1 μg/mL, as the transfection control) and either NF-κB-Luc (1 μg/mL) or AP-1-Luc constructs (1 μg/mL) using polyethylenimine transfection reagent for 24 h [35] , [36] were incubated with the indicated concentration of CK or PMA (100 nM) for another 24 h. The cells were collected and lysed to measure luciferase reporter gene activity using a luciferase assay system in accordance with the manufacturer’s instructions. All luciferase activities were normalized to β-galactosidase activity.…”
Section: Methodsmentioning
confidence: 99%
“…To measure the mRNA levels of target genes, total RNA was isolated from cells by Qiagen lysis solution (Qiagen, Maryland, USA) and transcribed into cDNA by Go Script reverse transcription process (Promega) according to the manufacturer's instructions and as described previously 67 . Quantitative real time-PCR was then performed using a Light Cycler 2.0 (Mannheim, Germany) using absolute QPCR SYBR green capillary mix system (Thermo Scientific, UK) at 95 °C for 15 min, with successive 40 cycles of 95 °C for 15 s, 56 °C for 30 s, and 72 °C for 45 s. The mRNA level of target gene was normalized to the value of glyceraldehyde-3-phosphate dehydrogenase (GAPDH).…”
Section: Methodsmentioning
confidence: 99%